SPIRITUAL EXERCISES, SACRAMENTAL IMAGINATION, AND AESTHETIC PEDAGOGY - Firmansyah, Antonius (Sanata Dharma University, 2023)
How can we relate the experience of encountering God during the Spiritual Exercises and our experiences after we return to our daily life? Juxtapositioning the two, we can find that sacramental imagination is the bridge between the Spiritual Exercises and the realities of daily life. The Spiritual Exercises provide us with the spiritual discipline to make our sacramental imagination alive. It is also this sacramental imagination that we relive every time we participate in a sacramental celebration. In the Spiritual Exercises, through applying our sacramental imagination, we are invited to engage with the development of our commitment to God. The level of awareness in this regard will be an indicator for the flourishing of our aesthetic self. Similarly, in the life of the sacraments of the Church, our polished and trained sacramental imagination will guide us to see the beauty of becoming a person ever more committed to the love of God and others.